2018
DOI: 10.4081/jphia.2018.860
|View full text |Cite
|
Sign up to set email alerts
|

The health-related impacts and costs of violence against women and girls on survivors, households and communities in Ghana

Abstract: Past research on violence in Ghana primarily discusses domestic violence and some types of sexual violence, but lacks a comprehensive analysis of violence against women and girls (VAWG) and its wider costs and impacts. Our study on the social costs of VAWG is a unique contribution, which aims to fill that gap. Through indepth interviews (IDIs) and focus group discussions (FGDs) with adult women and men, we explored the health impact of VAWG and the resulting social and economic consequences on survivors, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A possible explanation has been advanced in qualitative research conducted in Ghana. 32 In this study, researchers found that women in positions of leadership, who tend to have greater social networks, would hide violence they experienced to avoid being seen as unworthy of their roles. If it were known, their qualities as leaders would be contested, and they would have to give up their responsibilities within the community.…”
Section: Discussionmentioning
confidence: 86%
“…A possible explanation has been advanced in qualitative research conducted in Ghana. 32 In this study, researchers found that women in positions of leadership, who tend to have greater social networks, would hide violence they experienced to avoid being seen as unworthy of their roles. If it were known, their qualities as leaders would be contested, and they would have to give up their responsibilities within the community.…”
Section: Discussionmentioning
confidence: 86%
“…The most common public stigmatizing response identified ( n = 14), also exerted from the victim’s family and professionals, was holding women responsible for IPV when they disclosed abuse and looked for help (Barnett et al, 2016, Kenya; Childress et al, 2022, Kyrgyzstan; Mannell et al, 2018, Afghanistan; Thurston et al, 2016, China; among others). Women were blamed for the violence either for provoking it—if they did not fulfill the assigned gender role, such as being an obedient wife and faithful to the husband (Alvarado et al, 2018, Ghana; Furr, 2014, India; Muuo et al, 2020, Kenya; Thurston et al, 2016, China), for choosing the wrong husband (Alvarado et al, 2018, Ghana; Thurston et al, 2016, China), or because something was wrong with their character (Alvarado et al, 2019, Pakistan; Snell-Rood, 2015, India). In keeping with the psychological characteristics of women, if they appeared too strong or too weak, they could be blamed (Thurston et al, 2016, China).…”
Section: Resultsmentioning
confidence: 99%
“…It was also very common to make the victim feel ashamed if she disclosed the abuse ( n = 11) (Alvarado et al, 2018, Ghana; Mannell et al, 2018, Afghanistan; Snell-Rood, 2015, India; Thurston et al, 2016, China; among others). This occurred with the general public as well as family members to victims (Childress et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…A study in 2018 through in-depth interviews and focus group discussions with adult men and women in Ghana explored the health impacts of gender-based violence and the implications for the survivors, families and communities [13]. They revealed physical injuries and disability, as well as impacts on mental health such as anxiety and thoughts of suicide as health-related impacts of gender-based violence [13].…”
Section: Health Outcomes Associated With Gender-based Violencementioning
confidence: 99%
“…A study in 2018 through in-depth interviews and focus group discussions with adult men and women in Ghana explored the health impacts of gender-based violence and the implications for the survivors, families and communities [13]. They revealed physical injuries and disability, as well as impacts on mental health such as anxiety and thoughts of suicide as health-related impacts of gender-based violence [13]. Also, congruent with this study's finding is the reports from a study on GBV in 2013 which showed that the most reported social health impact of gender-based violence was stigmatization 23.2%, isolation and poor social relationship 16.35% [14].…”
Section: Health Outcomes Associated With Gender-based Violencementioning
confidence: 99%